2022
DOI: 10.1186/s13031-022-00445-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying transferable lessons from cholera epidemic responses by Médecins Sans Frontières in Mozambique, Malawi and the Democratic Republic of Congo, 2015–2018: a scoping review

Abstract: Background Cholera epidemics occur frequently in low-income countries affected by concurrent humanitarian crises. Evaluations of these epidemic response remains largely unpublished and there is a need to generate evidence on response efforts to inform future programmes. This review of MSF cholera epidemic responses aimed to describe the main characteristics of the cholera epidemics and related responses in these three countries, to identify challenges to different intervention strategies based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In particular, incomplete line lists, high population density, inadequate staffing for case load, and supply stock outs greatly hindered teams’ ability to access case households and appropriately target neighbor households according to the SOPs. Many of these key challenges identified herein align with other research on NGO-led cholera outbreak responses, including need for adequate staffing, supplies, staff training, mechanisms to enable reaching case households, and coordination [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 70%
“…In particular, incomplete line lists, high population density, inadequate staffing for case load, and supply stock outs greatly hindered teams’ ability to access case households and appropriately target neighbor households according to the SOPs. Many of these key challenges identified herein align with other research on NGO-led cholera outbreak responses, including need for adequate staffing, supplies, staff training, mechanisms to enable reaching case households, and coordination [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 70%
“…Household spot checks and CATI recipient and implementer interviews indicated major challenges with the delivery of WASH intervention materials. Most studies of CATIs and other cholera rapid response delivery programs have reported a variety of challenges with the complete delivery of WASH materials, including logistical and financial constraints [30,33,49]. Incomplete delivery of WASH materials has the potential to both decrease the effectiveness of a CATI and to decrease trust between recipients and CATI teams, as has been reported previously [30].…”
Section: Discussionmentioning
confidence: 97%
“…Previously published qualitative research from this study and reviews by UNICEF and Médecins Sans Frontières identified implementation challenges that may mediate CATI effectiveness such as high caseloads, incomplete line lists, stockouts, inadequate staffing, insufficient transportation, household refusals, security constraints, and high population density [ 14 , 52 , 53 ]. In Borno, the high population density resulted in cholera incidence that was 3 and 5 times greater than in Adamawa and Yobe, respectively, and translated into more households in a 150 m radius and increased travel time.…”
Section: Discussionmentioning
confidence: 99%